1999
DOI: 10.1053/euhj.1998.1444
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of three presentations of acute myocarditis in young men in military service. A 20-year experience

Abstract: AimsThe incidence of myocarditis is uncertain as diagnostic criteria have been vague. We evaluated the incidence of myocarditis presenting in three well defined forms (mimicking myocardial infarction, presenting as dilated cardiomyopathy, and as a cause of sudden death) in young men in military service over a 20-year period. Methods and ResultsThe study population consisted of 672 672 Finnish men at a mean age of 20 years conscripted from 1977-1996. All those suspected of having myocardial disease were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 33 publications
6
67
1
4
Order By: Relevance
“…In conclusion, in contrast to the experience of Moores et al 11 and associates, we corroborate Neelakandan, Sunday, and Kanthimanthi's [24][25][26][27][28][29] clinical observation that low cardiac output syndrome can complicate any method of surgical pericardial drainage even in patients with apparently normal myocardium and preoperative hemodynamic status. Therefore these patients require close postoperative monitoring for the first 24 hours, preferably in the intensive care unit, and aggressive treatment in case low cardiac output develops.…”
Section: Discussionsupporting
confidence: 82%
“…In conclusion, in contrast to the experience of Moores et al 11 and associates, we corroborate Neelakandan, Sunday, and Kanthimanthi's [24][25][26][27][28][29] clinical observation that low cardiac output syndrome can complicate any method of surgical pericardial drainage even in patients with apparently normal myocardium and preoperative hemodynamic status. Therefore these patients require close postoperative monitoring for the first 24 hours, preferably in the intensive care unit, and aggressive treatment in case low cardiac output develops.…”
Section: Discussionsupporting
confidence: 82%
“…In a study investigating individuals suspected of myocarditis from >670 000 male military recruits with a mean age of 20 years, 98 cases had myocarditis symptomatically similar to myocardial ischemia, 1 case had sudden death, and 9 cases had DCM within the initial stages of clinical disease. 10,11 Furthermore, Japanese investigators revisited 20 years of autopsy records and reported a incidence of 0.11% and 0.007% for nonspecific myocarditis and giant cell myocarditis, respectively. 12 Another retrospective study of 17 162 autopsy postmortem records demonstrated that myocarditis can be easily overlooked in an unsuspected number of cases if a standardized method of sampling is not followed, suggesting that myocarditis prevalence is often underestimated.…”
Section: Scope Of Importance (Epidemiology Cause and Consequences)mentioning
confidence: 99%
“…First, the study population was relatively small; however this reflects the low incidence of the disease. 5 Second, endomyocardial biopsy, which is considered the gold standard for the diagnosis of myocarditis, 32 was not performed; however, all included patients had cMRI findings consistent with AM, in agreement with current criteria. 6 Moreover, according to current guidelines, endomyocardial biopsy is not indicated in patients with suspected AM presenting without heart failure symptoms and preserved LV systolic function.…”
Section: Study Limitationsmentioning
confidence: 80%
“…7 Among patients with Takotsubo cardiomyopathy, which is characterized by a typical pattern of LV dysfunction, significant LGE is conversely usually absent. 23,24 Electrocardiographic repolarization changes in infarctlike myocarditis have been described 5,25,26 ; STE, attributed to epicardial inflammatory injury, is followed by gradual STsegment normalization and subsequent variable occurrence of T-wave inversion, attributed to epicardial damage. Finally, the ECG normalizes, with resolution of T-wave abnormalities; of note, development of Q wave is rarely observed.…”
Section: Electrocardiography In Infarct-like Myocarditis and Relationmentioning
confidence: 99%